2017
DOI: 10.1186/s12940-017-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of high apparent temperature on spontaneous preterm delivery: a case-crossover study

Abstract: BackgroundDespite the prediction that temperatures are expected to increase in the future, little is known about the health effects of increasing temperatures on pregnant women. The objective of this study was to investigate the impact of apparent temperature on spontaneous preterm delivery (PTD).MethodsA case-crossover study of 14,466 singleton spontaneous preterm deliveries occurring between January 1, 1995 and December 31, 2009 among Kaiser Permanente Northern California (KPNC) members was conducted. Preter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 61 publications
2
37
1
2
Order By: Relevance
“…This exclusion is analogous to case-crossover designs, which have proven to be valuable tools in further evaluating the potential impacts of other perinatal exposures. 8,9 In the absence of randomized trials, we agree with Hutcheon and Harper 6…”
supporting
confidence: 64%
“…This exclusion is analogous to case-crossover designs, which have proven to be valuable tools in further evaluating the potential impacts of other perinatal exposures. 8,9 In the absence of randomized trials, we agree with Hutcheon and Harper 6…”
supporting
confidence: 64%
“…We also included season at blood draw, skin color and ethnicity, since these were hypothesized to be strongly related to vitamin D status and there is increasing evidence of an association with perinatal outcome. Seasonal variations in respiratory and viral infections, as well as in the temperature, impact on preterm birth [37][38][39][40], while skin color is related to ethnicity, which has an independent effect on preterm birth and SGA; recent research suggests that skin tone may also be directly relevant to the investigation of perinatal outcomes [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The strong association between short-term temperature exposure and PTB in Detroit, Michigan, USA was consistent with several other studies’ observed associations between PTB or diminished gestational age and temperature exposures within the week prior to delivery at regionally high temperatures. Regions in which these associations have been found include Central Australia (8.3% at 40°C daily maximum temperature),11 Northern California, USA (11.6% increase for a 5.6°C increase in weekly average AT in the warm season),34 Alabama, USA (32.4% increase with two consecutive days of daily mean temperatures above the 98 th percentile),39 Barcelona, Spain (5-day reduction in average gestational age with heat index above the 99 th percentile),8 Rome, Italy (1.9% increase per 1°C increase in maximum AT in the prior 2 days and 19% increase during heat waves),40 Brisbane, Australia (13% to 100% increase during heat waves), in an aggregated sample of 12 US cities (12% to 16% increase with 2.8°C increase in prior week),12 in Southern China (7% increase with previous-week temperatures above 95 th percentile)10 and in a multi-city USA sample (2% increased PTB risk with extreme heat in the prior 4 days) 41…”
Section: Discussionmentioning
confidence: 91%
“…Case-crossover analysis is commonly used in studies of PTB and temperature 12 13 34. Because PTB is not a rare event in this particular population, the case-crossover ORs would not approximate risk ratios.…”
Section: Methodsmentioning
confidence: 99%